Does Operative Time Affect Infection Rate in Primary Total Knee Arthroplasty? - Naranje, Sameer (Clin Orthop Relat Res, 2014)
BACKGROUND: Prolonged operative time may increase the risk of infection after total knee arthroplasty (TKA). Both surgeon-related and patient-related factors can contribute to increased operative times. QUESTIONS/PURPOSES: The purpose of this study was to determine (1) whether increased operative time is an independent risk factor for revision resulting from infection after TKA; (2) whether increasing body mass index (BMI) increased operative time; and (3) whether increasing experience substantially decreased operative time. METHODS: We retrospectively evaluated primary TKAs from our joint registry between March 2000 and August 2012. Cox proportional hazard models were used to assess the relationship between operative time and revision resulting from infection after accounting for age, sex, BMI, and Agency for Healthcare Research and Quality comorbidity score. Of 9973 instances of primary TKA, 73 underwent revision surgery for infection (0.73%). RESULTS: After accounting for the confounders of age and sex, operative time was not found to have a significant effect; a 15-minute increase in operative time increased the hazard of revision resulting from infection by only 15.6% (p = 0.053; 95% confidence interval, 0.0%–34.0%). In addition, a five-unit increase in BMI was found to increase mean operative time by 1.9 minutes, on average, regardless of sex (p < 0.0001). Operative time decreases with increasing experience but appears to plateau at approximately 300 surgeries. CONCLUSIONS: Operative time is only one of many factors that may increase infection risk and may be influenced by numerous confounders. Increasing BMI increased operative time but the effect was modest. The effect of increasing experience on operative duration of this common procedure was surprisingly limited among our surgeons. LEVEL OF EVIDENCE: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.